Emerging epidemic of iatrogenic Acute Flaccid Paralysis in children under 15 years in Uganda - Kisakye, Annet; Ndungutse, David; Byarugaba, Justus; Naddumba, Edward.K.; Mbabazi, William; Bakamutumaho, Barnabas; Bwogi, Josephine; Bakainaga, Andrew; Seruyange, Rachel; Mwesigye, Innocent; Ndugwa, Christopher M. (Pan African Medical Journal, 2012)
Poliomyelitis a differential diagnosis of Acute Flaccid Paralysis (AFP) is a major disability. The prevalence of AFP associated with an intramuscular gluteal injection (s) among children below 15 years of age with fever reported through the AFP surveillance system between 2002 and 2008 in Uganda was studied. Methods A cross sectional study using AFP surveillance data. Any child aged below 15 years, who developed sudden flaccid paralysis between 1st January 2002 and 31st December 2008 was enrolled. NPEC conducted a desk review of completed AFP investigation forms for final classification. A case of an Injection Related Paralysis was defined as sudden onset of flaccid paralysis setting in within 72 hours of receipt of a gluteal intramuscular injection.
Keywords: Acute Flaccid Paralysis; Fever; Emerging epidemic; Latrogenic; Poliomyelitis; Gluteal injections